Acidic tumor microenvironment in human melanoma - Böhme, Ines; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2016)
One characteristic of solid tumors such as malignant melanoma is the acidification of the tumor microenvironment. The deregulation of cancer cell metabolism is considered a main cause of extracellular acidosis. Here, cancer cells utilize aerobic glycolysis instead of oxidative phosphorylation even under normoxic conditions, as originally described by Otto Warburg. These metabolic alterations cause enhanced acid production, especially of lactate and carbon dioxide (CO2 ). The extensive production of acidic metabolites and the enhanced acid export to the extracellular space cause a consistent acidification of the tumor microenvironment, thus promoting the formation of an acid-resistant tumor cell population with increased invasive and metastatic potential. As melanoma is one of the deadliest and most metastatic forms of cancer, understanding the effects of this extracellular acidosis on human melanoma cells with distinct metastatic properties is important. The aim of this review was to summarize recent studies of the acidification of the tumor microenvironment, focusing on the specific effects of the acidic milieu on melanoma cells and to give a short overview of therapeutic approaches.
EVALuna2:4736